Genetic factors underlying the risk of bortezomib induced peripheral neuropathy in multiple myeloma patients - Corthals, Sophie L.; Kuiper, Rowan; Johnson, David C.; Sonneveld, Pieter; Hajek, Roman; Holt, Bronno van der; Magrangeas, Florence; Goldschmidt, Hartmut; Morgan, Gareth J.; Avet-Loiseau, Hervé (Haematologica, the hematology journal, 2011)
Bortezomib induced peripheral neuropathy is a dose-limiting side effect and a major concern in the treatment of multiple myeloma. To identify genetic risk factors associated with the development of this side effect in bortezomib treated multiple myeloma patients, a pharmacogenetic association study was performed using a discovery set (IFM 2005-01; n=238) and a validation set (HOVON65/GMMG-HD4 and a Czech dataset; n=231). After multiplicity correction, none of the 2,149 single nucleotide polymorphisms tested revealed any significant association with bortezomib induced peripheral neuropathy. However, 56 single nucleotide polymorphisms demonstrated an association with bortezomib induced peripheral neuropathy with pointwise, uncorrected significance. Pathway analysis of these polymorphisms demonstrated involvement of neurological disease (FDR